ETHNONATIONAL EXTREMISM: OUTLOOK FACTORS AND ISSUES IN COUNTERING - S. I. Grachev; S. N. Molkov (Современная наука и инновации, 2022)
The article deals with monitoring and analyzing set of causes of ethnonational extremism in Russia. It explores concepts, views and factors contributing to extremist ideologies which target collective conscious of Russian people, youth in particular. The authors highlight issues in education and upbringing when forming civic self-consciousness, relations between minorities and nations, tolerance and anti-extremist outlook of young people